High yield expression, characterization, and biological activity of IFNα2-Tα1 fusion protein. Issue 3 (15th March 2020) - Aslam, Muhammad Shahbaz; Gull, Iram; Mahmood, Malik Siddique; Iqbal, Muhammad Mudassir; Abbas, Zaigham; Tipu, Imran; Ahmed, Aftab; Athar, Muhammad Amin
Abstract: The use of interferon α-2 in combination with thymosin α-1 shows higher anti-cancer effect in comparison when both are used individually because of their synergistic effects. In this study we produced an important human interferon α-2-thymosin α-1 (IFNα2-Tα1) fusion protein with probable pharmaceutical properties coupled to its high-level expression, characterization, and study of its biological activity. The IFNα2-Tα1 fusion gene was constructed by over-lap extension PCR and expressed in Escherichia coli expression system. The expression of IFNα2-Tα1 fusion protein was optimized to higher level and its maximum expression was obtained in modified terrific broth medium when lactose was used as inducer. The fusion protein was refolded into its native biologically active form with maximum yield of 83.14% followed by purification with ∼98% purity and 69% final yield. A band of purified IFNα2-Tα1 fusion protein equal to ∼23 kDa was observed on 12 % SDS-PAGE gel. The integrity of IFNα2-Tα1 fusion protein was confirmed by western blot analysis and secondary structure was assessed by CD spectroscopy. When IFNα2-Tα1 fusion protein was subjected to its biological activity analysis it was observed that it exhibits both IFNα2 & Tα1 activities as well as significantly higher anticancer activity as compared to IFNα-2 alone.